Synthesis of an iron-doped 3D-ordered mesoporous cobalt phosphide material toward efficient electrocatalytic overall water splitting. Issue 16 (17th July 2020) - Meng, Suci; Sun, Shichao; Qi, Yue; Jiang, Deli; Wei, Wenxian; Chen, Min
Abstract : The development of porous metal phosphides with abundant active sites is of great importance for efficient electrocatalytic water splitting. Abstract : The development of porous metal phosphides with abundant active sites is of great importance for efficient electrocatalytic water splitting. In this work, three-dimensional (3D)-ordered mesoporous iron-doped cobalt phosphide ( meso -Co2− x Fe x P) was prepared by a nanocasting strategy using SBA-15 as the hard template combined with a subsequent phosphidation. The unique mesoporous structure of the meso -Co2− x Fe x P electrocatalyst resulted in the exposure of abundant active sites and favorable mass transfer for the electrocatalytic process. Due to the synergy effects of the mesoporous structure and ternary component, the meso -Co2− x Fe x P exhibited outstanding electrocatalytic activity with low overpotentials of 93.7 mV and 266.4 mV at a current density of 10 mA cm −2 for HER and OER, respectively. In addition, meso -Co2− x Fe x P showed excellent overall water splitting activity with an external voltage of 1.58 V at a current density of 10 mA cm −2, superior to the electrolytic cell consisting of 20% Pt/C and RuO2, demonstrating it has great potential for practical application in overall water splitting.